2019
DOI: 10.1177/1024529419845810
|View full text |Cite
|
Sign up to set email alerts
|

The collateral liquidity problem in contemporary finance and the resurrection of quantity theory

Abstract: Since the 2008 crisis, the liquidity of collateral has become a serious concern for financial market institutions and regulators due to its increased importance in risk and cash flow management. Surprisingly, market participants mobilise old-fashioned economic theory, such as Irving Fisher's quantity theory of money in their discussions of how to deal with the new problems of collateral liquidity. Today, 'collateral is the new cash', as one sector report claims, marking a shift from a quantity theory of money … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A repo transaction is a reversible secured loan, in which a financial agent sells an asset to another agent at one price "and commits to repurchase the same or another part of the same asset from the second party at a different price at a future date" (ICMA, 2014). In addition to being used for monetary policy purposes, repos have become more and more popular in private markets since the 1990s primarily due to "technical innovations, Basel regulation and International Capital Market Association (ICMA) harmonization" (Krarup, 2019).…”
Section: The Role Of Government Bonds In Repo Transactions (And For E...mentioning
confidence: 99%
See 1 more Smart Citation
“…A repo transaction is a reversible secured loan, in which a financial agent sells an asset to another agent at one price "and commits to repurchase the same or another part of the same asset from the second party at a different price at a future date" (ICMA, 2014). In addition to being used for monetary policy purposes, repos have become more and more popular in private markets since the 1990s primarily due to "technical innovations, Basel regulation and International Capital Market Association (ICMA) harmonization" (Krarup, 2019).…”
Section: The Role Of Government Bonds In Repo Transactions (And For E...mentioning
confidence: 99%
“…This excess liquidity emerged organically as the Eurosystem began buying government bonds -although they were not the only instruments -on considerations other than fiscal ones. The motivation of these acquisitions is inherently related to the role of collateral of government bonds in repurchase agreements (repos) (Krarup, 2019). Therefore, if the Maastricht Treaty argued the importance of monetary independence and the prohibition of government bond purchases, the Euro crisis revealed that this independence is obsolete and that the Eurosystem's posture is influenced by the yield of government bonds.…”
Section: Introductionmentioning
confidence: 99%
“…This pushed the ECB to buy corporate bonds and other assets hitherto considered too insecure and volatile for use as collateral (Klooster and Fontan 2019). Indeed, one of the things that broke down with the financial crisis and the ensuing European debt crisis was the pre-2008 relationship between collateral and credit (money), specifically how it was organised in repo lending, government borrowing and collateralisation mechanisms (Mehrling et al 2015, Gabor 2016, Krarup 2019a, Sissoko 2019. This situation has revealed what Mehrling (2013) This new role has changed the image of monetary policy.…”
Section: Breakdown Of Monetary Policy and (Re-)manifestation Of The Ementioning
confidence: 99%
“…The ideas-practice conception tends to presuppose an opposition between a sphere of highly consistent doctrinal thought in (academic) economic theory and a sphere of pragmatic inconsistency and the politics of strategic interests. By contrast, taking the tensions, contradictions, paradoxes and conceptual insecurities of neoliberal economic thinking seriously suggests that 'epistemic problems' (Krarup 2019a) may account for some of the variation and doctrinal inconsistencies encountered in market formation and integration processes, which have otherwise been ascribed to contingencies of practice. Instead of seeing 'ideational factors' as more or less coherent theoretical doctrines competing for political influencesuch as German ordoliberalism (Bonefeld 2012), French dirigisme (Clift 2012) or Chicago School imperialism (Bartalevich 2016) -we could ask how the problems characteristic of certain types of economic thought are deployed across academic and political spheres.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation